Most quadratic functions(which is what you have there, to a degree of 2) are solved using factoring and the zero product law. If you can not factor then you have to use the quadratic formula or graph it. However this one can be factored.
It's pretty simple to just factor it by inspection but I use the chart method, if you know decomposition that works as well.
Factoring gives us,
![(2x + 1)(x - 3) = 0](https://tex.z-dn.net/?f=%282x%20%2B%201%29%28x%20-%203%29%20%3D%200)
Then you set each factor to 0 and solve for x,
![2x + 1 = 0](https://tex.z-dn.net/?f=2x%20%2B%201%20%3D%200)
![2x = - 1](https://tex.z-dn.net/?f=2x%20%3D%20%20-%201)
![x = \frac{ - 1}{2}](https://tex.z-dn.net/?f=x%20%3D%20%20%5Cfrac%7B%20-%201%7D%7B2%7D%20)
And the second one,
![x - 3 = 0](https://tex.z-dn.net/?f=x%20-%203%20%3D%200)
![x = 3](https://tex.z-dn.net/?f=x%20%3D%203)
The solutions to this equation are
x = -1/2, 3
Answer: 27
Step-by-step explanation:
The given sequence : 13, 24, 35, ....
Here, first term : a= 13
Common difference: d=24-13 =11
The nth term of arithmetic sequence is given by :-
![a_n=a+(n-1)d](https://tex.z-dn.net/?f=a_n%3Da%2B%28n-1%29d)
It is given that the nth term is 299, so put
![299=13+(n-1)11](https://tex.z-dn.net/?f=299%3D13%2B%28n-1%2911)
Subtract 13 from both sides , we get
![286=(n-1)11](https://tex.z-dn.net/?f=286%3D%28n-1%2911)
Divide both sides by 11, we get
![26=n-1](https://tex.z-dn.net/?f=26%3Dn-1)
Add 1 on both sides , we get
![n=27](https://tex.z-dn.net/?f=n%3D27)
Hence, the value of n= 27
<span>Let r(x,y) = (x, y, 9 - x^2 - y^2)
So, dr/dx x dr/dy = (2x, 2y, 1)
So, integral(S) F * dS
= integral(x in [0,1], y in [0,1]) (xy, y(9 - x^2 - y^2), x(9 - x^2 - y^2)) * (2x, 2y, 1) dy dx
= integral(x in [0,1], y in [0,1]) (2x^2y + 18y^2 - 2x^2y^2 - 2y^4 + 9x - x^3 - xy^2) dy dx
= integral(x in [0,1]) (x^2 + 6 - 2x^2/3 - 2/5 + 9x - x^3 - x/3) dx
= integral(x in [0,1]) (28/5 + x^2/3 + 26x/3 - x^3) dx
= 28/5 + 40/9 - 1/4
= 1763/180 </span>
Rewind the "mind movie" of what happened. She added $74 to her account and then had $192. Back it up by subtracting the $74 from $192.
192 - 74 = 118
Answer:
x = 4, -2 1/2
Step-by-step explanation:
factors:
(2x + 5) (x - 4)
set each factor equal to zero:
2x + 5 = 0
2x = -5
x = -5/2
x - 4 = 0
x = 4